Ethnic differences in metabolic achievement between Māori, Pacific, and European New Zealanders with type 2 diabetes. (July 2022) - Yu, Dahai; Cai, Yamei; Levi Osuagwu, Uchechukwu; Pickering, Karen; Baker, John; Cutfield, Richard; McKree Jansen, Rawiri; Orr-Walker, Brandon J.; Sundborn, Gerhard; Zhao, Zhanzheng; Simmons, David
Highlights: Ethnic disparity on diabetes control target in NZ over 20 years is less addressed. Māori and Pasifika T2DM patients achieved better SBP and TC over 20 years. New Zealand European achieved better glycaemic control target over 20 years. New anti-hyperglycemia treatments, and care integration are needed to reduce disparities. Abstract: Aims: To compare variations in metabolic target achievement by ethnicity (Europeans, Māori and Pasifika) among patients with type 2 diabetes (T2DM) in Auckland, New Zealand (NZ) between 1994 and 2013. Methods: 32, 237 patients were enrolled. Adjusted marginal difference (European as reference) of systolic blood pressure (SBP), body mass index (BMI), HbA1c and total cholesterol, alongside the proportion achieving metabolic targets were estimated using multivariable mixed effect models at baseline, 1-, 2-, 3-, 4-, and 5-years, adjusted for covariates. Results: Compared with Europeans, Māori and Pasifika had continuously, significantly higher HbA1c (by 0.3% (+3.5 mmol/mol) and 0.6% (+6.8 mmol/mol) respectively and BMI (+1.5 and +0.3 kg/m 2 respectively) but lower SBP (−1.8 and −3.4 mmHg respectively) and TG (-0.03 and −0.34 mmol/L respectively), and insignificantly TC (+0.004 and +0.01 respectively), by 5-years of follow-up. While 49% Europeans were within target HbA1c, this was achieved by only 30% Māori and 27% Pasifika. Conversely, 41% Europeans, 46% Māori and 59% Pasifika achieved the SBP target (all P  < 0.0001). Conclusions: Managing hyperglycemia appears to be more challenging than treating hypertension and dyslipidemia among Māori and Pasifika. New anti-hyperglycemia treatments, addressing health literacy, socioeconomic and any cultural barriers to management and self-management are urgently needed to reduce these disparities.